Perceived cultural distance in intercultural service encounters: does customer participation matter?. Issue 5 (10th January 2018) - Ang, Tyson; Liou, Ru-Shiun; Wei, Shuqin
Abstract : Purpose: This paper aims to investigate if perceived cultural distance (PCD) negatively affects service quality and customer satisfaction through customers' social judgements of the service providers' warmth and competence in intercultural service encounters (ICSE), and if this negative effect can be mitigated through customer participation (CP). Design/methodology/approach: A 2 × 2 between-subjects experimental design with an online consumer panel was conducted using a series of intercultural service encounter scenarios (in the weight loss service context) to manipulate CP (high vs low) and pictures of service providers to induce PCD (high vs low). Findings: As hypothesized, in the context of ICSE, PCD negatively impacts customers' social judgements of the service providers' warmth and competence, which in turn influence service quality and customer satisfaction. However, the negative impact of PCD is alleviated when the level of CP is high. Research limitations/implications: Using a single service context (weight loss services) may restrict the generalizability of findings. Future research may explore other service contexts. Practical implications: To improve customers' experience, managers in service firms with multicultural customers may create more engagement opportunities by designing the service delivery process in ways in which more CP and involvement is allowed. Originality/value: This research is among the first to highlight the importance of consumers' social judgements about culturally dissimilar service providers, which at baseline come with disadvantages but that can be altered through marketing actions (e.g. enhanced CP).